2021
DOI: 10.1007/s41999-021-00469-5
|View full text |Cite
|
Sign up to set email alerts
|

Probing pharmacists’ interventions in Long-Term Care: a systematic review

Abstract: Aim To investigate pharmacists' interventions and impact at institutional Long-Term Care (LTC) settings, particularly the therapeutic outcomes in elderly populations. Findings LTC pharmacists deliver a comprehensive set of activities, especially in clinical pharmacy (e.g. medication review, deprescribing) and education, addressing elderly populations under LTC and their therapeutic needs. Message Pharmacists' expertise in medicines optimisation is a useful resource in improving healthcare towards institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…Existing systematic reviews have focused on one of two main areas: (1) Evaluating the impact of specific healthcare providers (e.g., pharmacists [15], specialist practitioners [16,17], physiotherapists [18]) in LTCHs. For example, Barker (2018) found that the addition of a specialist practitioner, either a doctor or nurse, to supplement usual primary care, has the potential to improve health outcomes for LTCH residents [16]; or (2) Evaluating the impact of interventions specific to health conditions, which may include several healthcare providers within the model, for example nonpharmalogical interventions for dementia [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Existing systematic reviews have focused on one of two main areas: (1) Evaluating the impact of specific healthcare providers (e.g., pharmacists [15], specialist practitioners [16,17], physiotherapists [18]) in LTCHs. For example, Barker (2018) found that the addition of a specialist practitioner, either a doctor or nurse, to supplement usual primary care, has the potential to improve health outcomes for LTCH residents [16]; or (2) Evaluating the impact of interventions specific to health conditions, which may include several healthcare providers within the model, for example nonpharmalogical interventions for dementia [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Masnoon et al identified 42 tools for assessment of the appropriateness of prescribing [19]. To address the apparent scarcity of PATs specifically designed for LTC, we have decided to identify PATs previously used in the LTC context [28]. Additionally, we tried to reduce the set of PATs for panelists' assessment to avoid loss of richness during meeting discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing-Assessment Tools were identified in studies reporting pharmacist-led interventions in institutional LTC settings from published primary sources summarized in a recent systematic review, published elsewhere (Figure 1) [28]. Additionally, a manual search of relevant references from the retrieved papers was undertaken.…”
Section: Literature Review and Prescribing-assessment Tools Identificationmentioning
confidence: 99%
“…This assessment instrument is based on the International Classification of Functioning, Disability and Health (ICF) [29]. Each of the 31 questions is valuated on a Likert scale from 1 to 5 points: (1) No disability: 0-4%; (2) Mild disability: 5-24%; (3) Moderate disability: 25-49%; (4) Severe disability: 50-95%; and (5) Complete disability: 96-100%. From these 31 items, 10 items measure body functions, 17 items measure body structure, and 4 items measure environmental factors.…”
Section: Case Study: Evaluation Of Functional Profile Using the Elder...mentioning
confidence: 99%
“…Every day, healthcare professionals need to assess large numbers of patients-not only those with chronic or degenerative diseases but also those with long-term or chronic conditions [1]. This requires a constant reassessment of patients, especially for the aging population, among whom chronic and degenerative diseases and dysfunctions are more common and more frequent.…”
Section: Introductionmentioning
confidence: 99%